2015
DOI: 10.11607/ijp.4345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Framework in an Implant-Supported Full-Arch Fixed Prosthesis: 3D Finite Element Analysis

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 0 publications
2
45
0
3
Order By: Relevance
“…44 Moreover, there are studies which define that a zirconia infrastructure presents a similar biomechanical response to a titanium infrastructure, 34 while other reports define that more rigid materials are less damaging to the bone tissue. 45 These studies which compare implant infrastructures generally use the mechanical properties of the elastic modulus and the Poisson's coefficient of the simulated materials. 34,45 The elastic modulus and the Poisson's coefficient are properties related to the elasticity and plasticity of each material, allowing more or less displacement depending on the applied force.…”
Section: Discussionmentioning
confidence: 99%
“…44 Moreover, there are studies which define that a zirconia infrastructure presents a similar biomechanical response to a titanium infrastructure, 34 while other reports define that more rigid materials are less damaging to the bone tissue. 45 These studies which compare implant infrastructures generally use the mechanical properties of the elastic modulus and the Poisson's coefficient of the simulated materials. 34,45 The elastic modulus and the Poisson's coefficient are properties related to the elasticity and plasticity of each material, allowing more or less displacement depending on the applied force.…”
Section: Discussionmentioning
confidence: 99%
“…9 Likewise, the implant prosthesis metal framework is thought to play a significant role on the durability of the prosthesis and the veneering material. 13 Specifically, it is needed for acrylic reinforcement, reduce the bulk of framework and allow for cleansability of the prostheses. 3,4,13 This is more important in high stress regions such as cantilevers where the acrylic veneer will be subjected to heavy tensile stresses.…”
Section: Introductionmentioning
confidence: 99%
“…13 Specifically, it is needed for acrylic reinforcement, reduce the bulk of framework and allow for cleansability of the prostheses. 3,4,13 This is more important in high stress regions such as cantilevers where the acrylic veneer will be subjected to heavy tensile stresses. 3,14,15 Conversely, several authors indicated that the efficiency of metal reinforcement is dependent on the thickness, the rigidity, the position of the metal structure, and the design of the retentive features.…”
Section: Introductionmentioning
confidence: 99%
“…In implant prosthodontics, frameworks are used to improve the prosthesis rigidity and stiffness, reducing possible complications such as prosthesis fractures while rigidly splinting the implants together . Moreover, thanks to a rigid framework a more aesthetic prosthesis can be realised, especially when the prosthodontic space is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fibre frameworks may be considered as a viable alternative to the metal ones and showed less marginal bone loss around implants and a greater implant survival rate during the observation period. KEYWORDS: dental implants, carbon fibre-reinforced composite, prosthodontics framework, immediate loading, dental prosthesis, cohort study Accepted for publication 9 February 2017 Background In implant prosthodontics, frameworks are used to improve the prosthesis rigidity and stiffness, reducing possible complications such as prosthesis fractures while rigidly splinting the implants together (1). Moreover, thanks to a rigid framework a more aesthetic prosthesis can be realised, especially when the prosthodontic space is limited.…”
mentioning
confidence: 99%